Pengaruh Faktor Fundamental Terhadap Harga Saham Bank Dan Lembaga Keuangan Islam Indonesia - Yusmaniarti Yusmaniarti; Ummul Khair; Marini Marini; Esy Rahmawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This This study aims to examine the effect of fundamental factors consisting of ROA, EPS, and BOPO on stock prices in Islamic banking and Islamic financial institutions in Indonesia during the 2018-2020 period. The formulation of the problem in this study is how the effect of ROA, EPS, and BOPO on stock prices. The purpose of this study is to determine the effect of ROA, EPS and BOPO on stock prices. This type of research uses a quantitative data design with secondary data. The research sample uses the total sampling method, which is a sampling technique if all members of the population are used as samples. The research sample is the financial statements of Islamic banks and Islamic financial institutions originating from the last 3 years from 5 Islamic banking companies and 7 Islamic financial institution companies with research data totaling 36 data (3 years x 12 sample companies). The data collection method uses documentation and literature taken from www.idx.co.id. Data analysis used is descriptive statistical test and hypothesis testing. The results showed that ROA, EPS and BOPO had no effect on stock prices. This can be seen from the ROA p-values 0.419, EPS p-values 0.130 and BOPO p-values 0.146 which are greater than the public significance level of 0.05 . Meanwhile, ROA, EPS and BOPO have no simultaneous effect on stock prices.